Sosialisasi dan Pelatihan Pendaftaran Hak Cipta dengan Sistem POP HC di Kota Tasikmalaya - Maya Ruhtiani; Yuris Tri Naili; Purwono Purwono; Iin Dyah Indrawati (LPPM Universitas Harapan Bangsa Purwokerto, 2022)
Someone's copyrighted work is the absolute right of the creator who is named with copyright. Basically, a copyrighted work can be used alone or transferred to others through a legal transition. The transition can be economically beneficial because the copyright holder must pay royalties to the owner. Basically, not everyone is aware of the existence of a transfer of rights that can be one of the protection of one's work can be done by means of copyright registration as evidenced by a certificate of copyright registration issued by the DGIP. The method used is by socialization and training directly to the representatives of artists in the city of Tasikmalaya. Socialization and training activities are aimed at providing an understanding of copyright registration and providing training for owners of copyrighted works to be able to register their own copyrighted works using the POP HC application that has been made by the DGIP to facilitate the recording of copyright on a copyrighted work